Containment of Antibiotic REsistance—measures to improve antibiotic use in pregnancy, childbirth and young children (CAREChild): a protocol of a prospective, quasiexperimental interventional study in Lao PDR. Issue 11 (19th November 2020) - Machowska, Anna; Sihavong, Amphoy; Eriksen, Jaran; Vongsouvath, Manivanh; Marrone, Gaetano; Sychareun, Vanphanom; Hanson, Claudia; Keohavong, Bounxou; Brauner, Annelie; Mayxay, Mayfong; Kounnavong, Sengchanh; Lundborg, Cecilia Stalsby
Abstract : Introduction: Antibiotics are essential to treat infections during pregnancy and to reduce both maternal and infant mortality. Overall use, but especially non-indicated use, and misuse of antibiotics are drivers of antibiotic resistance (ABR). High non-indicated use of antibiotics for uncomplicated vaginal deliveries is widespread in many parts of the world. Similarly, irrational use of antibiotics is reported for children. There is scarcity of evidence regarding antibiotic use and ABR in Lao PDR (Laos). The overarching aim of this project is to fill those knowledge gaps and to evaluate a quality improvement intervention. The primary objective is to estimate the proportion of uncomplicated vaginal deliveries where antibiotics are used and to compare its trend before and after the intervention. Methods and analysis: This 3-year, prospective, quasiexperimental study without comparison group includes a formative and interventional phase. Data on antibiotic use during delivery will be collected from medical records. Knowledge, attitudes and reported practices on antibiotic use in pregnancy, during delivery and for children, will be collected from women through questionnaires. Healthcare providers' knowledge, attitudes and practices of antibiotics administration for pregnant women, during delivery and for children, will be collected via adapted questionnaires. Perceptions regarding antibiotics will be explored through focus group discussions with women and individual interviews with key stakeholders. Faecal samples for culturing of Escherichia coli and Klebsiella spp. and antibiotic susceptibility testing will be taken before, during and 6 months after delivery to determine colonisation of resistant strains. The planned intervention will comprise training workshops, educational materials and social media campaign and will be evaluated using interrupted time series analysis. Ethics and dissemination: The project received ethical approval from the National Ethics Committee for Health Research, Ministry of Health, Laos. The results will be disseminated via scientific publications, conference presentations and communication with stakeholders. Trail registration number: ISRCTN16217522 ; Pre-results.